Peningkatan Keterampilan Dalam Pengolahan Aneka Kue Kering Sebagai Solusi Meningkatkan Pendapatan Masyarakat di Kelurahan Reuloh Aceh Besar - Fitri, Aida; G, Harbiyah; Linu Ibrahim, Agusnawan; Fatma, Surya; Mazas, Ichsan Akmal (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
The training on making cookies in Reuloh Village, Ingin Jaya District, Aceh Besar Regency, aims to improve the skills of the community in entrepreneurship in the culinary field. This activity was carried out by the Lecturer Team of the Entrepreneurship Study Program, Faculty of Economics, Muhammadiyah University of Aceh. The training participants showed a significant increase in their knowledge and skills in making cookies. The survey results showed that 85% of participants were interested in starting a cookie business, which could increase the income of the local community and open up opportunities for people who want to start and expand culinary-based businesses. The expected output of this community service activity is to improve the skills and knowledge of the community, especially housewives and small business actors in Reuloh Village, Ingin Jaya District, in making cookies. In addition, this activity aims to encourage them to be able to develop culinary businesses and as teachers, the results of this activity will be published in a journal.